THE ROLE OF BUDGET PLANNING, SIPD, AND HUMAN RESOURCE COMPETENCE IN ENHANCING FINANCIAL PERFORMANCE: EVIDENCE FROM A PROVINCIAL GOVERNMENT AGENCY - Sari, Istiana Dwi; Sam, Iskandar; Olimsar, Fredy (Jurnal Cakrawala Akuntansi, 2026)
This research examines the influence of budget planning, the Regional Government Information System (SIPD), and human resource competence on the financial performance of the Regional Agency for Financial and Revenue Management (BPKPD) in Jambi Province. The research is motivated by variations in revenue realization and operational expenditure efficiency observed between 2021 and 2023. A quantitative survey method was employed, with data collected from 10 respondents across six technical divisions. Financial performance was measured using indicators related to budget realization, expenditure efficiency, and compliance with financial management procedures. The data were analyzed using multiple linear regression with SPSS 27. The results indicate that budget planning, SIPD implementation, and human resource competence have a positive and significant effect on financial performance, both individually and explain more than half of the variation in financial performance. These findings provide empirical evidence that effective planning, adequate use of information systems, and competent human resources are important factors in improving financial performance within provincial government agencies.